Application of Fuzzy Immune Algorithm and Soft Computing in the Design of 2-DOF PID Controller. (7th June 2022) - Ding, Ning; Prabhakar, Priti; Khosla, Anita; Jagota, Vishal; Ramirez-Asis, Edwin; Singh, Bhupesh Kumar
Abstract : To solve the difficulty in selecting the crossover probability and mutation probability in genetic algorithms, a fuzzy immune algorithm based on adaptive estimation of crossover probability and mutation probability in a fuzzy reasoning system is proposed, and it is used in the parameter optimization design of a two-degree-of-freedom PID controller. According to the experiment and simulation results, classic genetic algorithm evolution tends to halt after 37 generations, with a fitness value of 7.135, whereas fuzzy genetic algorithm evolution tends to stop after 20 generations, with a fitness value of 7.486. The 2-DOF PID controller that was created can give the system strong target value following and interference suppression features at the same time.